H-Man: customized handles for a 2D planar robot - Xiang, Yu (2015)
The project was to design a customized control handle for a 2D planar robot, which would provide a stable and comfortable working situation. The paper aimed to find out how the different shapes of handle effects to the stress distribution and user comfort. In the project, computer aided engineering technique was used to build a human hand model according to the order of bone, muscle, and hand. In order to define a nonlinear reaction force with a variable changing with time, the User-defined subroutine to specify Amplitudes (UAMP) , a subroutine of ABAQUS, was used to present a nonlinear function of time.